Numerical Investigation of Extended Stern to Reduce Resistance of Planing Hull - Samuel , Samuel; Manik, Parlindungan; Praja, Rizal Kurnia; Tuswan, Tuswan; Paryanto, P; Djaeni, Mohamad; Sari, Dian Purnama (Transactions on Maritime Science, 2023)
The attributes of a high-speed vessel depend on various factors, such as trim angle, speed, center of gravity, and deadrise angle. The ship's trim angle will affect the ship's drag performance. Attempts to control trim have been made by adding stern appendages and modifying the hull. This study aims to analyze the performance of deep-V planing-hull ship drag by modifying the ship's stern. The stern modification investigation was carried out by adding length to the stern based on angles of 100, 200, and 300. This investigation evaluates resistance, trim, and heave while ignoring changes in ship displacement. The prediction of resistance and ship movements was simulated using the Reynold Averaged Navier-Stokes (RANS) equations to solve the problem. Numerical simulation applied the Computational Fluid Dynamics (CFD) based on finite volume method with an overset of techniques. Validation studies ensured numerical simulations have good accuracy based on comparisons with experimental model tests conducted by previous researchers. The pressure distribution caused by the extended stern affected the ship's drag, further demonstrating a better trim control. The results of the stern modification simulation revealed that the resistance was reduced at Fr 0.58–0.87. Extended sterns with an angle of 30° indicated the best results, with a resistance reduction percentage of 26% at Fr 0.58. However, drag increased at Fr speeds > 1.45 as the ship's speed increased.